Azathioprine Induced Pancreatitis in a Patient with Co-Existing Autoimmune Pancreatitis and Hepatitis - Venkatesh, Preethi G K; Navaneethan, Udayakumar (JOP. Journal of the Pancreas, 2011)
Context Azathioprine induced pancreatitis usually runs a benign self limited course with rapid disappearance of signs and symptoms upon with drawl of the drug. Azathioprine is used in treating relapses in patients with autoimmune pancreatitis and maintenance of remission in autoimmune hepatitis. Acute pancreatitis complicated by symptomatic pseudocysts requiring drainage is not usually associated with drug induced pancreatitis. The risk of azathioprine use in patients with underlying disease of pancreas including autoimmune pancreatitis is unclear. Case report We report here a case of an African American patient with co-existing autoimmune pancreatitis and autoimmune hepatitis who developed azathioprine induced acute pancreatitis complicated by a large symptomatic pseudocyst compressing the duodenum requiring a cystoduodenostomy. Conclusions Future studies to investigate the risk of azathioprine induced pancreatitis in the presence of underlying disease of the pancreas including autoimmune pancreatitis are required to further understand the safety of azathioprine in this sub group of patients. Image: Pseudocyst in the head of the pancreas compressing the common bile duct and duodenum.